(a + b) (a - b) = a^2 - b^2
Hence, (a + b) = (a^2 - b^2) / (a - b)
If a = b, the above formula is invalid, because you would be dividing by 0 and would get an undefined value.
That is, a = b means a - b = 0.
2007-01-05 17:01:32
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Well if a=b, the second statement (the hence part) is proven to be false because that would make it undefined. Any value divided by 0 is undefined (if a and b are equal, their difference is zero). Thus when a=b, there is an instance in which the hence statement is false and cannot be trusted to work.
2007-01-05 17:04:17
·
answer #2
·
answered by hmm123 2
·
0⤊
0⤋
I hope u mean (a+b)(a-b)=a^2 - b^2.
therefore, a+b = (a^2 - b^2)/(a - b).
since when a=b the LHS becomes 0/0 form, we can't use directly, but instead we can apply the limit on both sides that a tends to b. that is a is very very close to b but not equal to b.
hence as someone stated before, we can LHS as (a+b)(a-b)/(a-b) and hence = a+b.
2007-01-05 19:21:21
·
answer #3
·
answered by Smart prash 2
·
0⤊
0⤋
if a=b then the numerator of lhs becomes a^2-b^2=o
and the denominator a-b=o.
therefore the lhs becomes =0/0 which is an invalid mathematical term. hence for a=b the eqution is not valid
2007-01-05 17:10:40
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
(a+b)(a-b) = a^2. b^2 hence (a+b) =a^2-b^2/a-b what if a=b:?
I assume you mean (a+b)(a-b) = a^2 - b^2.
Hence a+b = (a^2 -b^2)/(a-b)
So a+b = [(a+b)(a-b)]/(a-b) = a+b
By canceling out the denominator we avoid dividing by 0 when a=b.
2007-01-05 17:08:19
·
answer #5
·
answered by ironduke8159 7
·
0⤊
0⤋
If a = b, then a - b = 0. Thus, your second equation would be undefined because it would have a 0 in the denominator, which isn't allowed.
2007-01-05 17:02:11
·
answer #6
·
answered by purpicita_LM_es_fg_MDK 2
·
0⤊
0⤋
in u r statement :
(a+b)(a-b) = a^2. b^2 is not correct i think (a+b)(a-b) = a^2 - b^2.
if it is true then if a=b then the answer is not defined since 0/0=undefined.
2007-01-05 21:24:15
·
answer #7
·
answered by Rags 2
·
0⤊
0⤋
When a=b, then
2a*2b=2a*2a=4a^2
But a^2-b^2=a^2-a^2=0
Therefore the id will not be valid.
If you have any problem with mathematics, then u can contact me. I am an specialist of mathematics.
2007-01-05 21:03:02
·
answer #8
·
answered by Rambo 1
·
0⤊
0⤋
(a+b)(a-b)=a^2-b^2.....for any values of a&b
But,(a+b)=a^2-b^2/(a-b)....for any a not equal to b
2007-01-05 21:34:26
·
answer #9
·
answered by Ryan A 1
·
0⤊
0⤋
answer will be zero
2007-01-07 17:01:50
·
answer #10
·
answered by angel 2
·
0⤊
0⤋